Clearing the haze : helping families face teen addiction - Thurstone, Christian; Tatum, Christine (Lanham : Rowman & Littlefield, 2015)
Often it is difficult for parents to recognize when their child is abusing alcohol, using illegal drugs, or in trouble with other substances that are hazardous to their health, safety, and wellbeing. Clearing the Haze is a guide designed to help parents determine whether their child may have a substance problem and, if so, how to begin to address it. The book includes the voices and insight of experts in substance abuse counseling, young people in recovery, and parents who have lived the nightmare of adolescent addiction. The book moves readers through an overview of adolescent brain development, the warning signs of drug use and addiction, treatment options, what families should expect of therapy, the basics of productive communication, and the difficulties of dealing lovingly with addicted teens. The authors encourage families entering the 12th step of "giving back" to consider advocacy for smarter public policies surrounding drug access and addiction treatment. They also provide a list of resources parents may find useful.
Foreword / Patrick J. Kennedy -- Why adolescent substance use is a big deal -- Parents' tools for planning, communicating, and monitoring -- What to do when you learn your child is using drugs -- When to seek treatment and what to look for in it -- Specific family objectives during treatment: The theory -- Specific family objectives during session: The practice -- How parents can help their adolescents not use substances -- Addiction is a chronic condition that requires chronic maintenance -- Taking care of you -- Advocating for adolescent substance prevention -- Additional resources -- Summary.
Includes bibliographical references and index.
Keywords: Teenagers -- Substance use; Substance abuse -- Treatment; Addicts -- Rehabilitation; Addicts -- Family relationships; Cloth or Hardcover; Self-Help.; Substance Abuse & Addictions -- Drugs; Mental Health; Psychopathology -- Addiction